(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the history of the emergence of Uzbek folk games is briefly covered, their importance in the healthy, spiritual and moral education of students is revealed, and the name of republican sports festivals and competitions that have become a tradition and are held in different regions of our country is given. It is emphasized that the leadership of the republic has a special role in the promotion of a healthy lifestyle in the Republic of Uzbekistan and in the spiritual and moral education of the young generation.